Inflation, Economic Growth, And Non-hydrocarbon Exports In Algeria - Bouzemlal ,Faiza (University of Eloued جامعة الوادي, 2025)
This study investigates the relationship between inflation, economic growth and non hydrocarbon exports in Algeria over the period 2000–2024, using an econometric approach including OLS models, stationary tests (ADF, KPSS) and the error correction model (ECM). The results obtained confirm the hypothesis on the existence of a long-term equilibrium relationship (cointegration) relationship between Algeria’s non-hydrocarbon exports (NHX) and a set of explanatory variables included in the estimated model, namely: inflation and economic growth (measured by GDP per capita). A positive and statistically significant effect was recorded for GDP per capita on non-hydrocarbon exports in the long run. On the other hand, it was found that Inflation has no statistically significant effect on non-hydrocarbon exports, neither in the short run or in the long run. Furthermore, the error correction model (ECM) indicated a gradual adjustment towards equilibrium with approximately 29% of the deviation from equilibrium corrected each year.
مقال
Keywords: Non hydrocarbon exports; inflation; economic growth; GDP per capita; OLS model